Tinjauan Hukum Ekonomi Syariah Terhadap Praktik ShopeePayLater Sebagai Produk Fintech Kontemporer - Ifa Nurul Fauziah; Ahmad Zulfa Aulia Rahman; Muhammad Hafidz Faujan; Andhika Ulhaq Faturrahman (LPPM STEBIS YPII, 2025)
The development of financial technology (fintech) has brought various innovations in payment systems, including the PayLater service that allows consumers to make purchases with deferred payments. Shopee PayLater, as one of the contemporary fintech products, has become a phenomenon in Indonesian consumer behavior. This study aims to analyze the practice of Shopee PayLater from the perspective of Islamic economic law using qualitative methods. The research method used is a qualitative approach with descriptive analysis techniques through literature studies and normative-juridical studies of Islamic economic principles. The results of the study based on the literature review indicate that the practice of PayLater contains elements that potentially conflict with Islamic principles, particularly related to the concepts of usury and gharar, and can encourage excessive consumptive behavior that is detrimental to Muslim consumers. This study recommends the need to develop a Sharia fintech model that is more in line with Islamic economic principles.